Comparison of Behavior and Genetic Structure in Populations of Family and Kenneled Beagles - Turcsán, Borbála; Tátrai, Kitti; Petró, Eszter; Topál, József; Balogh, Lajos; Egyed, Balázs; Kubinyi, Eniko (Frontiers in Veterinary Science, 2020)
In dogs, the social and spatial restriction associated with living in a kennel environment could lead to chronic stress and the development of abnormal behaviors ('kennel-dog syndrome'). However, little is known about how kenneled dogs differ from their conspecifics living as pets in human families. In the current study, using a test battery exposing the dogs to novel stimuli, we compared the behavior of three groups of beagles: (1) kenneled dogs living in a restricted environment with limited human contact (N=78), (2) family dogs living in human families as pets (N=37), and (3) adopted dogs born in the kenneled population but raised in human families (N=13). We found one factor comprising most of the test behaviors, labelled as Responsiveness. Family dogs and adopted dogs scored higher in Responsiveness than kenneled dogs. However, 23% of the kenneled dogs were comparable to family and adopted dogs based on a cluster analysis, indicating a similar (positive) reaction to novel stimuli, while 77% of the kenneled dogs were unresponsive (mostly immobile) in at least part of the test. To assess if the behavioral difference between the family and kenneled dogs could be due to genetic divergence of these two populations and/or to lower genetic diversity of the kenneled dogs, we analyzed their genetic structure using 11 microsatellite markers. We found no significant difference between the populations in their genetic diversity (i.e., heterozygosity, level of inbreeding), nor any evidence that the family and kenneled populations originated from different genetic pools. Thus, the behavior difference between the groups more likely reflects a G x E interaction, that is, the influence of specific genetic variants manifesting under specific environmental conditions (kennel life). Nevertheless, some kenneled individuals were (genetically) more resistant to social and environmental deprivation. Selecting for such animals could strongly improve the welfare of kenneled dog populations. Moreover, exploring the genetic background of their higher resilience could also help to better understand the genetics behind stress- and fear-related behaviors.